The fight against greenwashing in the European Union - Silva, Daniel (2021)
Greenwashing, a practice through which companies try to create an image of doing more for the environment than they actually are, is a possible threat to the current environmental goals of the European Union. In this article, we intend to analyse the tools and instruments foreseen by the European Union to combat this phenomenon, particularly from the current ideological line of the European Green Deal and the New Consumer Agenda